2006
DOI: 10.1016/j.cub.2005.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation between Mitotic Kinesins Controls the Late Stages of Cytokinesis

Abstract: Cell division is regulated by protein kinases of the Cdk, Polo, and Aurora families. Although it has long been established that temporal control is central to the coordinated action of these kinases, the importance of spatial regulation has only recently been appreciated and is still poorly understood. The kinesin-6 family motor protein MKlp1 is a key regulator of cytokinesis and an ideal substrate for studying spatially regulated protein-phosphorylation events. MKlp1 is negatively regulated by Cdk1 phosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
101
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 24 publications
4
101
0
Order By: Relevance
“…The first gene we examined in this group, Kif23, is a motor molecule known to be involved in cytokinesis (Nislow et al, 1992;Raich et al, 1998;Neef et al, 2006), a process important in axolotl (Rao et al, 2009, Heber-Katz et al, 2013 and zebrafish regeneration (Poss et al, 2002(Poss et al, , 2004. Kif23, also known as MKLP1, is part of a critical complex formed at the midzone or midbody and associates with CYK-4 in the central spindlin (Glotzer, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The first gene we examined in this group, Kif23, is a motor molecule known to be involved in cytokinesis (Nislow et al, 1992;Raich et al, 1998;Neef et al, 2006), a process important in axolotl (Rao et al, 2009, Heber-Katz et al, 2013 and zebrafish regeneration (Poss et al, 2002(Poss et al, , 2004. Kif23, also known as MKLP1, is part of a critical complex formed at the midzone or midbody and associates with CYK-4 in the central spindlin (Glotzer, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that this forced entry in mitosis is a trigger for a catastrophic mitosis (Fig. 2 ) because podocytes cannot assemble an efficient mitotic spindle due to poor expression of Aurora kinase B, which is essential for cytokinesis [75, 76]. Indeed, occurrence of abnormally mitotic podocytes and micro-multinucleation was demonstrated by electron microscopy in mice models of adriamycin nephropathy, a model of FSGS [75].…”
Section: The Podocyte’s Catastrophe: Lost Cell Cycle Controlmentioning
confidence: 99%
“…In addition, phosphorylation of MKLP1 by Aurora B is important to prevent the protein from being sequestered back in the nucleus as cells enter interphase. 252 It is interesting to note that many components required for cytokinesis are located in the nucleus or associated with Golgi apparatus during interphase (Fig. 2) and thus localization of cytokinesis components to the midbody could require sustained phosphorylation that prevents the proteins from being resequestered by these structures as cells exit mitosis.…”
mentioning
confidence: 99%
“…Treatment of human cells with a small molecule inhibitor of Aurora B in early mitosis inhibits localization of MKLP1 (and its binding partner MgcRacGAP) to the central spindle. 266 However, addition of an Aurora inhibitor at later stages of mitosis inhibits phosphorylation of MKLP1 without disrupting its localization, 252,267 yet perturbs cytokinesis completion, indicating that MKLP1 must remain phosphorylated to permit abscission. How phosphorylation regulates MKLP1 is not completely clear, as MKLP1 is phosphorylated at multiple sites that may have distinct effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation